Biodegradable films of gelatin incorporated with bentonite clay ionically modified - Garrido, Murillo Alves; Leite, Ricardo Henrique de Lima; Aroucha, Edna Maria Mendes; Santos, Franciso Klebson Gomes (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
Biofilms are biodegradable and/or edible films made from biopolymers. The application of biofilms as packaging is directly related to its characteristics, and to their interactions with the product and the environment. Proteins are promising materials, due to the wide range of functional properties. Gelatine is an attractive biomaterial, due to its large production and low cost. However, gelatine has limitations in its physicochemical properties when compared to synthetic polymers. The improvement of these properties was proposed in this study from the incorporation of bentonite clay in the gelatin films. In order to increase the interaction between clay and gelatin, clay was modified in the presence of a surfactant (sodium dodecyl sulfate), aiming at the basal spacing between the silicate layers. The films of gelatin with modified bentonite clay were characterized as bionanocomposite through analysis of Optical Microscopy (MO), Angle of Contact (AC), water vapor permeability (PVA), solubility, mechanical properties and humidity. The incorporation of bentonite clay into gelatin films reduced 40.8% of the water vapor permeability, and increased the rupture stress by 55%. The clay significantly improved the physicochemical properties of the biopolymer film.